2012
DOI: 10.1089/fpd.2012.1249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Treatments of Electron-Beam Irradiation and Addition of Leek (Allium tuberosum) Extract on Reduction of Pathogens in Pork Jerky

Abstract: This study investigated the combined effect of electron-beam irradiation and addition of leek (Allium tuberosum R.) extract on pork jerky inoculated with selected foodborne pathogens. Prepared pork jerky samples (control and samples with 1.0% leek extract) were inoculated with pathogens and subsequently irradiated at 0, 0.5, 1, 2, 3, and 4 kGy doses. In comparison with the control, samples with 1.0% leek extract showed significant reduction in the numbers of Escherichia coli, Listeria monocytogenes, and Salmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Reactive species are formed depending on the gas composition, and it has been reported that adding O 2 promotes the formation of reactive oxygen species (ROS) in the plasma, which plays the most important role in the inactivation of microorganisms among the various reactive species (Deng et al, 2006;Lee et al, 2006;Lee et al, 2012). As shown in Figure 2, the reactive O I, OH, and NO emissions were enhanced in the gas treatment by combination of N 2 + O 2 .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Reactive species are formed depending on the gas composition, and it has been reported that adding O 2 promotes the formation of reactive oxygen species (ROS) in the plasma, which plays the most important role in the inactivation of microorganisms among the various reactive species (Deng et al, 2006;Lee et al, 2006;Lee et al, 2012). As shown in Figure 2, the reactive O I, OH, and NO emissions were enhanced in the gas treatment by combination of N 2 + O 2 .…”
Section: Resultsmentioning
confidence: 97%
“…Liu et al (2008) reported that oxygen radicals can produce lipid oxidation byproducts including hexanal and malondialdehyde. However, there were no significant differences on the pH levels and lipid oxidation values of bacon and cooked egg white after APP treatment with different gas compositions (He or He + O 2 ) (Kim et al, 2011;Lee et al, 2012). Cooked egg white also shows no significant differences in sensory evaluation among gas compositions.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Kang et al [50] studied the efficacy of radiation treatment combined with leek (Allium tuberosum R.) extract on the survival of several food-borne pathogens inoculated in pork jerky. The authors used doses in the range of 0.5-4 kGy.…”
Section: Reducing Of Salmonella Spp In Ready-to-eat Foodsmentioning
confidence: 99%
“…Kang et al (2012) showed that S. typhimurium (Gram-negative) inoculated in pork jerky was sensitive to EB-irradiation combined with treatment with leek extract, while L. monocytogenes (Gram-positive) did not show sensitivity under the same conditions. Song et al (2009) reported that in fermented oyster, D 10 values for L. monocytogenes and Vibrio parahaemolyticus (Gram-negative) were 0.60 and 0.29 kGy for gamma irradiation and 0.69 and 0.29 kGy for EB, respectively.…”
Section: Effect Of Eb-irradiation On Growth Of Pathogens In Inoculatementioning
confidence: 99%